2016
DOI: 10.3171/2016.6.peds16200
|View full text |Cite
|
Sign up to set email alerts
|

Patient and operative factors associated with complications following adolescent idiopathic scoliosis surgery: an analysis of 36,335 patients from the Nationwide Inpatient Sample

Abstract: OBJECTIVE The aim of this study was to investigate the incidence of and factors associated with complications following idiopathic scoliosis surgery in adolescents. METHODS The Nationwide Inpatient Sample database was used to identify patients 10-18 years of age who had undergone spinal fusion for adolescent idiopathic scoliosis (AIS) from 2002 to 2011. Twenty-three unique in-hospital postoperative complications, including death, were examined. A series of logistic regressions was used to determine if any demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 32 publications
2
41
1
3
Order By: Relevance
“…These results mirror findings from other large population-based research demonstrating significant reductions in hospital LOS [7,8,17,20]. Vigneswaran et al in a study of surgical outcomes in individuals with idiopathic scoliosis, reported a decrease in average hospital LOS from 6.5 days in 1997 to 5.6 days in 2012 [8], which does not seem to be associated with higher complication rates [21].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results mirror findings from other large population-based research demonstrating significant reductions in hospital LOS [7,8,17,20]. Vigneswaran et al in a study of surgical outcomes in individuals with idiopathic scoliosis, reported a decrease in average hospital LOS from 6.5 days in 1997 to 5.6 days in 2012 [8], which does not seem to be associated with higher complication rates [21].…”
Section: Discussionsupporting
confidence: 81%
“…These deaths occurred only in patients with non-idiopathic scoliosis (n = 655) [29]. De la Garza Ramos (2016) found a seemingly high mortality rate of 0.12% among 36,335 individuals with adolescent idiopathic scoliosis during the inpatient stay [20]. In our study there were no deaths among individuals with adolescent idiopathic scoliosis.…”
Section: Discussioncontrasting
confidence: 40%
“…The morbidity rate was 2.9% in the present study, which was lower than those in previous studies, ranging from 3.7% to 14.9%. [ 8 12 , 14 ] This discrepancy possibly arose through underestimation in the present study, because mild complications might have been underreported in the database as is reported in other studies utilizing the same database. [ 19 21 ]…”
Section: Discussionmentioning
confidence: 59%
“…This study identified several predictive factors for postoperative complications, including male sex, comorbid diabetes, and use of allogeneic blood transfusion. De la Garza Ramos et al [ 12 , 13 ] reported that male sex was a risk factor for postoperative complications in pediatric fusion surgery. Roddy and Diab [ 22 ] revealed that unplanned readmission after fusion for pediatric spinal deformity was significantly higher in male patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation